2021
DOI: 10.21203/rs.3.rs-593801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Budget Constrained Machine Learning for Early Prediction of Adverse Outcomes for COVID-19 Patients

Abstract: Background: Machine learning (ML) based risk stratification models of Electronic Health records (EHR) data may help to optimize treatment of COVID-19 patients, but are often limited by their lack of clinical interpretability and cost of laboratory tests. We develop a ML based tool for predicting adverse outcomes based on EHR data to optimize clinical utility under a given cost structure. This cohort study was performed using deidentified EHR data from COVID-19 patients from ProMedica Healthcare in northwest Oh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…AI technologies that emphasize development of learning models while taking cost constraints into account are loosely called "budget-sensitive" learning models. 8,9 While all fields of medicine can benefit from such approaches, it can be argued that point-of-care diagnostics (POC), which highly values costeffectiveness, tends to benefit the most. Furthermore, a budget sensitive model synergizes well with the more recent wave of POC diagnostics that have incorporated more "smart" elements in the assay workflow.…”
Section: Introductionmentioning
confidence: 99%
“…AI technologies that emphasize development of learning models while taking cost constraints into account are loosely called "budget-sensitive" learning models. 8,9 While all fields of medicine can benefit from such approaches, it can be argued that point-of-care diagnostics (POC), which highly values costeffectiveness, tends to benefit the most. Furthermore, a budget sensitive model synergizes well with the more recent wave of POC diagnostics that have incorporated more "smart" elements in the assay workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of risk factors influencing disease severity is critical for efficient clinical management of COVID-19 patients. Studies have shown that risk factors, such as obesity, sex, and age are highly correlated with adverse outcomes in COVID-19 patients [1][2][3][4][5][6] . Furthermore, recent studies suggest such risk factors also may affect certain aspects of COVID-19 progression, specifically disease onset 7 and time-to-death 8 .…”
Section: Introductionmentioning
confidence: 99%